2009
DOI: 10.3945/ajcn.2009.27944
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption during pregnancy, prenatal mercury exposure, and anthropometric measures at birth in a prospective mother-infant cohort study in Spain

Abstract: The role of fish in fetal growth depends on the amount and type of fish consumed. The findings for mercury warrant further investigation in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
86
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 36 publications
10
86
2
1
Order By: Relevance
“…The results showed that the negative association with birth weight was stronger among women with the GSTM1 null genotype or with both GSTM1 and GSTT1 null genotypes (26) . Our finding of a negative association between maternal exposure to Hg during pregnancy and birth weight is in accordance with a study from a birth cohort in Spain, where high cord blood THg concentrations were inversely related with birth weight (24) . In the Spanish study, infants in the highest quartile of cord blood THg weighed on average 143?7 g less (95 % CI 2251?8 g, 235?6 g) than those in the first quartile, adjusted for intake of fish and seafood.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results showed that the negative association with birth weight was stronger among women with the GSTM1 null genotype or with both GSTM1 and GSTT1 null genotypes (26) . Our finding of a negative association between maternal exposure to Hg during pregnancy and birth weight is in accordance with a study from a birth cohort in Spain, where high cord blood THg concentrations were inversely related with birth weight (24) . In the Spanish study, infants in the highest quartile of cord blood THg weighed on average 143?7 g less (95 % CI 2251?8 g, 235?6 g) than those in the first quartile, adjusted for intake of fish and seafood.…”
Section: Discussionsupporting
confidence: 81%
“…In the Spanish study, infants in the highest quartile of cord blood THg weighed on average 143?7 g less (95 % CI 2251?8 g, 235?6 g) than those in the first quartile, adjusted for intake of fish and seafood. That study also indicated a possible increasing risk of delivering SGA babies with increasing THg, but the result was not statistically significant (24) . In most studies where no association between Hg exposure and birth weight is found, lack of adjustment for fish and seafood intake in the analysis may result in underestimation of both the toxicity of Hg and the nutritional benefits of eating fish products (52)(53)(54) .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The protective effect of a high adherence to MD in fetal growth in the INMA-Mediterranean cohort is in accordance with previous analyses within the INMA cohort in Valencia that have shown a significant increase in BW and BL in newborns of women with better diet during the first trimester based on the Alternate Healthy Eating Index (20) , and a positive association of vegetable intake during pregnancy with anthropometric measurements at birth (7) . Dietary patterns account for cumulative and interactive effects among nutrients, reflect real-world dietary preferences and may be particularly suitable for analysis in epidemiology of fetal growth in which many dietary components could be related with the outcome of interest (34) .…”
Section: Discussionsupporting
confidence: 78%